Feasibility and Short-Term Toxicity of a Consecutively Delivered Five Fraction Stereotactic Body Radiation Therapy Regimen in Early-Stage Breast Cancer Patients Receiving Partial Breast Irradiation - Liu, Yilan; Veale, Christopher; Hablitz, Diana; Krontiras, Helen; Dalton, Allison; Meyers, Korie; Dobelbower, Michael; Lancaster, Rachael; Bredel, Markus; Parker, Catherine; Keene, Kimberly; Thomas, Evan; et al. (Frontiers in Oncology, 2022)
Background: For appropriately selected early stage breast cancer patients, accelerated partial breast irradiation (APBI) yields equivalent rates of ipsilateral breast tumor recurrence (IBTR) with mixed results in patient rated cosmesis compared to whole breast radiotherapy depending on the technique utilized. When utilizing external beam radiotherapy for APBI, techniques to reduce target margins and overall treatment volume are potentially important to decrease rates of long term adverse cosmesis. Stereotactic body radiotherapy (SBRT) is a promising technique to deliver APBI because of its increased accuracy and sparing of uninvolved breast tissue. We report the initial results of a prospective clinical trial investigating feasibility, safety, and cosmetic outcomes of a daily 5 fraction SBRT regimen for APBI. Methods: Twenty-three patients with early stage breast cancer after lumpectomy who met APBI suitability were enrolled. During lumpectomy, a bioabsorbable 3D fixed array tissue marker was placed for enhanced visualization of the cavity boundaries. Clinical target volume (CTV) was defined as the delineable cavity plus a 1 cm isotropic expansion followed by a 3mm isotropic planning target volume (PTV) expansion. Patients received 30 Gy delivered in 5 planned consecutive daily fractions in either prone or supine positioning depending on individual anatomy.A maximum PTV of 124cc was allowed to minimize incidence of fat necrosis. Plans utilized 10MV flattening filter free (FFF) beams delivered on a Varian Edge linear accelerator. Local control, toxicity, and nurse/patient- scored cosmesis at pre-treatment baseline, 1 month post-treatment, and at subsequent 6 month intervals were recorded. Results: Twenty-three patients were accrued at the time of submission with median follow-up of 6 months. No patients experienced grade ≥3 acute toxicity. Of the 10 events reported probable to SBRT, 9 were grade 1 (n=9/10, 90%). There was no evidence of difference, deterioration or change in patient or nurse-scored cosmesis from baseline to 1 and 6 months post-treatment. One patient developed nodal failure shortly after APBI. Conclusions: Although longer followup is needed to assess long term toxicity and local control, this study demonstrated a 5-fraction SBRT regimen delivered over consecutive days is a safe, efficient, well-tolerated, and cosmetically favorable means of delivering APBI in suitable women.